Occurrence of skeletal malocclusions in Brazilian patients with dentofacial deformities - Boeck,Eloísa Marcantonio (2011)
In this study, a survey was conducted on the occurrence of skeletal malocclusions presented by patients of the Center for Research and Treatment of Buccofacial Deformities (CEDEFACE) in the city of Araraquara, SP, Brazil. The clinical charts of 381 patients with dentoskeletal deformities, who underwent combined orthodontic-surgical treatment in the period between 2000 and 2006, were reviewed. After sample selection (convenience method), based on the data of the pre- and post-surgical documentation, the number of patients was reduced to 171. For classification of the survey, the anteroposterior discrepancy (Class I, II and III), race, age, gender, absence or presence of asymmetry, vertical maxillary excess and maxillary biprotrusion were considered, in addition to determining in which bony base the surgical procedure was performed. Patients' documentations were analyzed by one examiner previously calibrated by repetition of the process until the method was considered adequate (intraclass correlation coefficient > 0.94). Patients' mean age was 23.59 (SD 6.93) years, the majority (102 patients) were women, and Caucasians (160 patients). Class III malocclusion was the most prevalent (81 patients). Asymmetry, vertical maxillary excess and biprotrusion were present in 54, 33, and 7 patients, respectively. The majority of surgeries for correction of dentoskeletal deformities were combined, involving the maxilla and mandible. In conclusion, Class III was the most prevalent skeletal deformity and Class I was the least prevalent; in general, the prevalence of skeletal deformities was higher in women; in the majority of patients with skeletal malocclusions there was a combination of maxillary and mandibular problems, which interferes directly in the decision regarding the most adequate treatment plan, and a higher incidence of asymmetry was observed in skeletal Class III; vertical excess occurred in a similar manner in Class II and III and there was a low incidence of biprotrusion among the malocclusions evaluated.